Coexistence Patterns Between Ants And Spiders In Grassland Habitats - András Márton Rákóczi (Universidade Estadual de Feira de Santana, 2014)
The ecological importance of both ants and spiders is well known, as well as the relationship between certain spiders and ants. The two main strategies ˗ myrmecomorphy (ant-mimicking) and myrmecophagy (ant-eating) ˗ that connect spiders to ants have been mostly studied at the behavioural level. However, less is known about how these relationships manifest at the ecological level by shaping the distribution of populations and assemblages. Our question was how ant-mimicking and ant-eating spiders associate with ant genera as revealed by field co-occurrence patterns. For both spider groups we examined strength and specificity of the association, and how it is affected by ant size and defence strategy. To study spider-ant association patterns we carried out pitfall sampling on the dolomitic Sas Hill located in Budapest, Hungary. Spiders and ants were collected at eight grassland locations by operating five pitfalls/location continuously for two years. To find co-occurrence patterns, two approaches were used: correlation analyses to uncover possible spider-ant pairs, and null-model analyses (C-score) to show negative associations. These alternative statistical methods revealed consistent co-occurrence patterns. Associations were generally broad, not specific to exact ant genera. Ant-eating spiders showed a stronger association with ants. Both ant-mimicking and ant-eating spiders associated more strongly with Formicine ants - species with formic acid or anal gland secretions, and had neutral association with Myrmicine ants - species with stings and cuticle defences.